Conservative Management of Congenital Eversion of the Upper Lid in a Nigerian Child - -, - (Pakistan Journal of Ophthalmology, 2018)
In PJO Vol. 28; Issue 4; 2012 the fig 1 was replicate in fig 2. The corrected figures are given below.